If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(-x-2)=-3x
We move all terms to the left:
6(-x-2)-(-3x)=0
We add all the numbers together, and all the variables
6(-1x-2)-(-3x)=0
We multiply parentheses
-6x-(-3x)-12=0
We get rid of parentheses
-6x+3x-12=0
We add all the numbers together, and all the variables
-3x-12=0
We move all terms containing x to the left, all other terms to the right
-3x=12
x=12/-3
x=-4
| 2(x=7)-10 | | 12+3v=4v | | 99u-20+1.5u=8.25 | | -14.7=-2.2+u/5 | | 2x-3+2x+5+4x=50 | | 8=7-2y | | 2(3x+5)+5x=5(2x+3 | | 20m=45 | | 2x+1+2x+3+2x+5+2x+7=96 | | 10=6c=4 | | 2x+1+2x+1+2x+1+2x+1=96 | | 4.2x+1=96 | | 3(m-1)=5(m+2) | | 8(4x-4)-32=5x-32 | | 13000=-125(t-122) | | 2y=-2/3y+15/y | | -5x-10=18+5x | | 3v+147=120 | | 5+0.57142857142(21+3x)=41 | | 6x-12=4+5x-16 | | -5.x+8=55 | | 4.4444444=24/x | | 40/9=20/x | | 16x-17=180 | | 40/9=24/x | | -4m+13m= | | 10x=3(2x+12) | | -2d+20=42 | | 525+y=600 | | 12h-36=24 | | (11x+23)=(14x-4) | | 10x+6+8x-6=180 |